197k views
0 votes
3 (m - 1) = 5m + 3 - 2m just solve it plz



dont answer if u dont know >:(

2 Answers

3 votes

Answer:

There is no answer to this question. (No Solution)

User Nishank Singla
by
6.2k points
4 votes

Answer:

No solution

Explanation:

To solve the equation, we would have to find the value of m that would make the equality true.

3(m - 1) = 5m + 3 - 2m

Distribute the 3 on the left side.

3m - 3 = 5m + 3 - 2m

Combine like terms on right side.

3m - 3 = 3m + 3

Add 3 to both sides.

3m = 3m + 6

Subtract 3m from both sides.

0 = 6

Since 0 does not equal 6, there would be no solution to the equation, since no value of m would make 0 = 6 true.

I hope you find my answer and explanation to be helpful. Happy studying.

User Duy Nguyen
by
5.8k points